Factor Affecting Corporate Social Responsibility Within Global Reporting Initiatives - Martin Gunawan (Trunojoyo University of Madura, 2018)
Many studies describe the Corporate Social Responsibility Disclosure (CSRD) that emerged since 2007 as obligation and deduction of earnings and requires listed companies to perform philantrophy as part of legitimacy act. This research conducted to determines the hypothesis factors of CSRD specified to Global Reporting Initiavites (GRI) standards in 2014 and 2015 that implemented framework GRI G4. The qualitative and quantitative findings using regression analysis test, best equation model, classic assumption test for 22 sustainability reporting showed current ratio, debt to equity, size, institutional ownership and age have significant effects. This research show increasing disclosure and the recurring topics of standardized CSRD from among members of GRI group.